(3MGTjI Ydi TQM GdefgLs - (3Ydj fhQ GdOjf GdRjGJis; (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdTGaYj , CHh jMji,J (B926 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY GdYdeG Edi CYdi ebGe hHYO agPg JYGdjb hahGFO JJYdb HTQM GdefgL s
(3BNQgG (B:s
(3hQLM GdGPQYi efgG hJUOjbI hEf EYJQa HGdMed eGde JeVi eOI dGjHbi GdMed ajgG eLjJkG hgPG gh GdeYJeO hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9277) s
Keywords: (3Gdabg GdESdGejs